Pembelajaran Lari Cepat Dengan Menggunakan Modifikasi Shuttle Run (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine "Is Modified Shuttle Run can improve learning outcomes Elementary School fifth grade students Cenggini 02 Subdistrict Balapulang Tegal 2014". This research method is a class action research by using two cycles, each cycle consisting of four stages, namely planning, action, observation and action planning reflection. The second cycle associated with the results achieved in the first cycle acts as an improvement effort of the cycle. The subjects of this study were fifth-grade students of elementary Negri Cenggini 02. Research conducted includes three domains, namely affective, cognitive and psychomotor addition to the observations made during the process of the learning process takes place. The results showed the affective, cognitive and psychomotor well categorized shows that the learning outcomes quick run using a modified shuttle run a positive impact as seen on mastery learning outcomes of students who exceed the predetermined KKM 75 In the first cycle the average value of students 75 , 71 in the second cycle the average value of 78.60 students, mastery learning in the first cycle reaches 64.29%, while in the second cycle reaches 92.86% mastery learning .mean mastery learning students has increased by 28.57%. It is concluded that learning to run faster by using a modified shuttle run has a positive effect, which can increase student interest and motivation to learn.